Question
upstudy study bank question image url

\( 1.3 \quad 2 x ^ { 2 } - 2 \geq 3 x \)

Ask by Gray Bates. in South Africa
Feb 20,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The solution is \( x \leq -\frac{1}{2} \) or \( x \geq 2 \).

Solution

Solve the equation \( 2x^2 - 2 \geq 3x \). Solve the inequality by following steps: - step0: Solve the inequality by testing the values in the interval: \(2x^{2}-2\geq 3x\) - step1: Move the expression to the left side: \(2x^{2}-2-3x\geq 0\) - step2: Rewrite the expression: \(2x^{2}-2-3x=0\) - step3: Factor the expression: \(\left(x-2\right)\left(2x+1\right)=0\) - step4: Separate into possible cases: \(\begin{align}&x-2=0\\&2x+1=0\end{align}\) - step5: Solve the equation: \(\begin{align}&x=2\\&x=-\frac{1}{2}\end{align}\) - step6: Determine the test intervals: \(\begin{align}&x<-\frac{1}{2}\\&-\frac{1}{2}2\end{align}\) - step7: Choose a value: \(\begin{align}&x_{1}=-2\\&x_{2}=1\\&x_{3}=3\end{align}\) - step8: Test the chosen value: \(\begin{align}&x<-\frac{1}{2}\textrm{ }\textrm{is the solution}\\&-\frac{1}{2}2\textrm{ }\textrm{is the solution}\end{align}\) - step9: Include the critical value: \(\begin{align}&x\leq -\frac{1}{2}\textrm{ }\textrm{is the solution}\\&x\geq 2\textrm{ }\textrm{is the solution}\end{align}\) - step10: The final solution is \(x \in \left(-\infty,-\frac{1}{2}\right]\cup \left[2,+\infty\right):\) \(x \in \left(-\infty,-\frac{1}{2}\right]\cup \left[2,+\infty\right)\) The solution to the inequality \(2x^2 - 2 \geq 3x\) is \(x \in (-\infty, -\frac{1}{2}) \cup [2, +\infty)\).

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Beyond the Answer

To solve the inequality \(2x^2 - 2 \geq 3x\), first, we can rearrange it to form a standard quadratic inequality. Move all terms to one side: \[2x^2 - 3x - 2 \geq 0\] Now, factor the quadratic expression. You want factors of \(-4\) (the product of \(2\) and \(-2\)) that add up to \(-3\). The factors \(-4\) and \(1\) work, so we can rewrite it as: \[(2x + 1)(x - 2) \geq 0\] Next, determine the roots by setting each factor to zero: 1. \(2x + 1 = 0 \Rightarrow x = -\frac{1}{2}\) 2. \(x - 2 = 0 \Rightarrow x = 2\) Now, we have critical points at \(x = -\frac{1}{2}\) and \(x = 2\). To solve the inequality, test intervals defined by these critical points: 1. \( (-\infty, -\frac{1}{2}) \) 2. \( (-\frac{1}{2}, 2) \) 3. \( (2, \infty) \) Choose test points from each interval and evaluate the inequality: - For \(x = -1\) (first interval): \( (2(-1) + 1)(-1 - 2) = (-1)(-3) = 3 \geq 0\) (True) - For \(x = 0\) (second interval): \( (2(0) + 1)(0 - 2) = (1)(-2) = -2 \geq 0\) (False) - For \(x = 3\) (third interval): \( (2(3) + 1)(3 - 2) = (7)(1) = 7 \geq 0\) (True) The solution set includes the intervals where the inequality holds and the roots themselves since the inequality is non-strict (≥0). Therefore, the solution is: \[ x \in \left(-\infty, -\frac{1}{2}\right] \cup [2, \infty) \]

Related Questions

Latest Algebra Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy